Optimizing the Supply Chain of Qiut Cireng MSME in Ragawacana Village-Kuningan Regency: A Community Development - Safriyana; Lukito, Adriel Jonathan; Nurmasruroh, Izzah; Gunawan, Jovan; Wijaya, Mutiara (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia’s economy by contributing to job creation, investments, and local growth. In Kuningan Regency, MSMEs such as Qiut Cireng face significant internal and external challenges that hinder their growth. Qiut Cireng, an MSME in Ragawacana Village, specializes in chicken-filled cireng but struggles with limited marketing, inadequate promotion, and operational inefficiencies. In response, the 2024 Community Development program by Universitas Prasetiya Mulya aimed to optimize Qiut Cireng’s business strategy, focusing on key aspects of its supply chain: operations, marketing, finance, and distribution. The program used a live-in period to gather primary data, allowing the implementation of improvements such as waste reduction in production, logo and packaging redesign, enhanced social media marketing, and improved financial record-keeping. The results revealed that while Qiut Cireng did not face major financial difficulties, limited production capacity and low demand were barriers to growth. The program successfully identified strategies to improve branding, product visibility, and sales channels, demonstrating that a comprehensive supply chain approach is crucial for MSME growth. Ongoing efforts are essential for ensuring the long-term success of Qiut Cireng and strengthening the role of MSMEs in Indonesia’s economy.